Handbook of Research on Transformative and Innovative Pedagogies in Education - Keengwe, Jared Sagini, editor 651831; IGI Global (Online service) 631983 (Hershey PA. : IGI Global, Information Science Reference, 2022)
The Handbook of Research on Transformative and Innovative Pedagogies in Education is a comprehensive reference that identifies and justifies the paradigm of transformative learning and pedagogies in education. It provides exemplars of existing transformative applications that, if used as partners to empower student learning, have the potential to dramatically engage students in a type of learning that better fits 21st century learners. Covering topics such as gamification, project-based learning, and professional development, this major reference work is an essential resource for pre-service and in-service teachers, educational technologists, instructional designers, educational administration and faculty, researchers, and academicians seeking pedagogical models that inspire students to learn meaningfully.